2008
DOI: 10.1098/rsta.2008.0213
|View full text |Cite
|
Sign up to set email alerts
|

Surface temperatures of the Mid-Pliocene North Atlantic Ocean: implications for future climate

Abstract: The Mid-Pliocene is the most recent interval in the Earth's history to have experienced warming of the magnitude predicted for the second half of the twenty-first century and is, therefore, a possible analogue for future climate conditions. With continents basically in their current positions and atmospheric CO 2 similar to early twenty-first century values, the cause of Mid-Pliocene warmth remains elusive. Understanding the behaviour of the North Atlantic Ocean during the Mid-Pliocene is integral to evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 71 publications
(104 reference statements)
5
18
0
Order By: Relevance
“…SSTs at U1313/DSDP 607, ODP 662 and ODP 958 show a lesser degree of warming at lower latitudes compared to the Mediterranean, which fits well with our understanding of Pliocene equator to pole temperature gradients (Fedorov et al, 2013). However, as in the Mediterranean (Herbert et al, 2015), the Gulf of Cadiz is notably warmer than PRISM data (Dowsett et al, 2009;Salzmann et al, 2011), which suggests that at least in this region the PRISM reconstruction should be adjusted toward warmer temperatures by as much as 5-6°C. In the case of Site U1313, we acknowledge that in the modern regime it is situated in slightly cooler than Site U1387 waters, which affects our comparison (Fig.…”
Section: Site U1387 In the Pliocene Frameworksupporting
confidence: 75%
“…SSTs at U1313/DSDP 607, ODP 662 and ODP 958 show a lesser degree of warming at lower latitudes compared to the Mediterranean, which fits well with our understanding of Pliocene equator to pole temperature gradients (Fedorov et al, 2013). However, as in the Mediterranean (Herbert et al, 2015), the Gulf of Cadiz is notably warmer than PRISM data (Dowsett et al, 2009;Salzmann et al, 2011), which suggests that at least in this region the PRISM reconstruction should be adjusted toward warmer temperatures by as much as 5-6°C. In the case of Site U1313, we acknowledge that in the modern regime it is situated in slightly cooler than Site U1387 waters, which affects our comparison (Fig.…”
Section: Site U1387 In the Pliocene Frameworksupporting
confidence: 75%
“…At low latitudes, the SST changes in the AOGCM can be relatively large compared to the difference between SST prescribed for the control and mid-Pliocene AGCM experiments and is more typical of the changes seen in future global climate model projections. The inability to reproduce the SST anomalies as indicated by proxy data in both the northern North Atlantic and the tropical regions may raise certain questions not only about the applicability of the proxy data, but also about the validity of the analogy between mid-Pliocene and late 21st century climate states (Dowsett et al, 2009a). However, we also have to keep in mind the simplifications made in our experimental design and consider how these may have a bearing on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that the warming is not linearly related to the value of oceanic heat transport: increasing from 0 to the present-day heat transport increases the surface temperature by 2.6 K, but only 0.6 K from the present day to 2 times present-day values. Closer to the present and already with the same continental configuration, Dowsett et al (1996Dowsett et al ( , 2009 argue that the warmer high-latitude ocean temperatures during the midPliocene (;3 Ma) can be explained by a more vigorous North Atlantic Deep Water formation and thermohaline circulation. Finally, Romanova et al (2006) found using an atmospheric general circulation model that reduced ocean heat transport contributed to global cooling during the Last Glacial Maximum.…”
Section: Introductionmentioning
confidence: 97%